2011
DOI: 10.1007/s10800-011-0329-5
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of bromate and perbromate on BDD anodes during electrolysis of aqueous systems containing bromide: first systematic experimental studies

Abstract: Bromide electrolysis was carried out on laboratory-scale cells in the range of 1-1,005 mg [Br -] dm -3 using boron-doped diamond (BDD) anodes. These studies were part of fundamental research activities on drinking water electrolysis for disinfection. Synthetic water systems were mostly used in the experiments, which varied the temperature between 5 and 30°C, the current density between 50 and 700 A m -2 , and the rotation rate of the rotating anode between 100 and 500 rpm (laminar regime). Hypobromite and brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Only small amounts of hypobromite were detected, always below 0.5 mg dm −3 , while bromite ions were not detected in the samples. This experimental evidence is in agreement with that obtained by Bergmann and coworkers, who reported a systematic study on the oxidation of bromide at BDD anodes: oxidation mediated by hydroxyl radicals and oxygen radicals was indicated as the main mechanism of conversion of bromides to bromates. The authors also found that perbromate ions were produced during the electrolyses with initial concentration of bromide of 288 mg dm −3 and current density at least equal to 200 A m −2 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Only small amounts of hypobromite were detected, always below 0.5 mg dm −3 , while bromite ions were not detected in the samples. This experimental evidence is in agreement with that obtained by Bergmann and coworkers, who reported a systematic study on the oxidation of bromide at BDD anodes: oxidation mediated by hydroxyl radicals and oxygen radicals was indicated as the main mechanism of conversion of bromides to bromates. The authors also found that perbromate ions were produced during the electrolyses with initial concentration of bromide of 288 mg dm −3 and current density at least equal to 200 A m −2 .…”
Section: Resultssupporting
confidence: 92%
“…To the best of our knowledge, few reports are present in the literature on the electrolysis of bromide ions with BDD anodes; Bergmann and coworkers have shown that, working at 200 A m −2 , the electrolysis of solutions containing about 150 ppm of bromide ions allows the formation of bromate ions with very high current efficiency …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disproportionation of Br 2 in water may go all the way to bromate (and even to perbromate) [75,76] via a series of reversible disproportionation steps coupled to acid-base reactions. The first step is believed to occur at a near neutral 4≤ pH≤8 via the following pathway:…”
Section: Resultsmentioning
confidence: 99%
“…Due to that, in employing such materials for remedying with wastewater, it is frequent that the pathways utilized to interpret the decomposition of organic compounds do not only take into account the direct oxidation via electron transfer on the anode surface but, most possibly, the mediated oxidation through a huge collection of oxidants produced from the various salts carried in the electrolyte, as well as ozone and hydrogen peroxide [21]. This begins to be an issue in disinfection due to the potential formation of toxic perchlorate [22] [23]; however, it is very favorable participation in the electrolysis of wastewater [24].…”
Section: Introductionmentioning
confidence: 99%